A New Application of Anuj Transform for Solving Partial Differential Equations (Journal of Humanitarian and Applied Sciences, 2023)
In this paper, we have applied Anuj transform to solve partial differential equations and derived the partial derivatives of the Anuj transform.
Keywords: Anuj Transform; Partial Differential Equations